Enhancing angiogenesis through secretomes: Insights from scratch wound assay - Madhura Shekatkar; Supriya Kheur; Shantanu Deshpande; Swapnali Sakhare; Avinash Sanap; Avinash Kharat; Ramesh Bhonde (Journal of Oral Biology and Craniofacial Research)
Background: This study uses a scratch wound healing assay to investigate the angiogenic potential of secretomes derived from dental mesenchymal stem cells (DMSCs). Angiogenesis, defined as the process of generating new blood vessels, plays a pivotal role in the mechanisms of tissue regeneration and repair. Methodology: We cultured DMSCs under standard conditions, collected the secretomes, and applied them to human endothelial cells cultured in a scratch-assay setup. Endothelial cell migration into the scratch area was observed and quantified over a 48-h period. Results were compared to controls treated with a standard growth medium. Results: Preliminary findings indicate that DMSC-derived secretomes of dental pulp significantly enhance the migration of endothelial cells compared to controls, suggesting a strong angiogenic potential. Conclusion: These findings show that DMSC secretomes from dental pulp can help with angiogenesis. This could have big effects on the development of new treatments for tissue repair and regeneration. This study provides valuable insights into the paracrine mechanisms through which DMSCs may contribute to angiogenesis, highlighting their potential in regenerative medicine applications.